2002
DOI: 10.1063/1.1464894
|View full text |Cite
|
Sign up to set email alerts
|

Results from a scaled final focus experiment for heavy ion fusion

Abstract: Negative chlorine ions from multicusp radio frequency ion source for heavy ion fusion applications Rev.A one-tenth-scale version of a final focus subsystem for a heavy-ion-fusion driver has been built and used for experimental tests of concept. By properly scaling the parameters that relate ion energy and mass, current, emittance, and focusing fields, the transverse dynamics of a representative driver final focus have been replicated in a small laboratory beam. Whereas the driver beam parameters considered are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Metal grids are a known method of generating electrons due to beam ion impact [1,2]. Depending on the angle of incidence, the yield of electrons ranges from ~10 to ~100 per primary ion, with the highest values at glancing angles [3].…”
Section: Neutralizing Gridmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal grids are a known method of generating electrons due to beam ion impact [1,2]. Depending on the angle of incidence, the yield of electrons ranges from ~10 to ~100 per primary ion, with the highest values at glancing angles [3].…”
Section: Neutralizing Gridmentioning
confidence: 99%
“…The peak power in the compressed pulse delivered to the target plane was measured at ~470 kW, with ~1.5 mJ in the ~5ns (FWHM) compressed pulse. 1 The {} braces denote that the magnetic field is scaled proportional to E b 1/2 to keep the rms beam envelope in the matching solenoids and un-neutralized drift sections unchanged for a space charge dominated beam. …”
Section: Effect On the Beammentioning
confidence: 99%
“…The Multiple Beam Experiment [6] accelerated four beams simultaneously from 200 keV to 0.9 MeV, and compressed them by a factor of 7. Experiments were also done to combine beams transversely [7], and focus them to a spot (in a 1/10 scale model in linear dimension of a driver focusing system) [8]. Finally, a target tracking experiment showed that targets could be injected and tracked into the target chamber accurately enough for the beams to properly hit the target [9].…”
Section: Status Of Heavy-ion Fusion Physicsmentioning
confidence: 99%
“…The key scaling parameter for beam transport is the dimensionless perveance defined as the ratio of the beam space charge to kinetic energy (K = 2I [27]. Previous neutralization experiments [26,28] have provided, to some degree, confirmation of this limit.…”
Section: Physics Of Neutralizationmentioning
confidence: 99%
“…An earlier experiment [26] examined the charge neutralization of a heavy ion beam by electrons drawn from a localized source as the beam was focused. The electron source was a glowing tungsten filament placed in the beam path, enabling the supply of thermionicallyemitted electrons inside of the beam.…”
Section: Introductionmentioning
confidence: 99%